NOVEL HAFALAN SHOLAT DELISA KARYA TERE LIYE - Candra Wijaya; Sri Rezeki Harahap (Universitas Dharmawangsa, 2020)
Given the importance of character in building strong human resources, the need for character education is carried out appropriately. It can be said that the formation of character is something that can not be separated from life. Therefore, care is needed by various parties, both by the government, the community, families and schools. Novels as a form of literary work are expected to bring up positive values for the audience so that they are sensitive to problems related to social life and encourage reading novels that can realize positive messages in the novel with good behavior in social life. When the world of education is considered to only pursue and prioritize the academic realm, so that it ignores moral issues and nobility. Literary work in the form of a novel entitled HSD by Tere Liye, seems to be a strategic intermediary for realizing the goal of instilling character education to students because in the novel contains values that must be straightened out.